2010
DOI: 10.1246/cl.2010.1256
|View full text |Cite
|
Sign up to set email alerts
|

Water-soluble Inclusion Complexes of [60]Fullerene Derivatives Using γ-Cyclodextrin

Abstract: Pyrrolidine and N,N-dimethylpyrrolidinium derivatives of C60 could be solubilized in water with the aid of γ-cyclodextrin. The complexes were found to be soluble in water at high concentrations over 1.5 mM. These solubility values are significantly higher than those of other C60 derivatives reported previously. Furthermore, these solutions are stable for at least one month at room temperature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…These γ‐CDx ⋅ C 60 derivative complexes are expected to broaden the potential applications of fullerenes. For example, C 60 derivatives 1 – 5 (Figure ) form 2:1 complexes with γ‐CDx through the HSVM method . The solubilities of the γ‐CDx ⋅ C 60 derivative complexes in water were in the following order: 5 (2.4×10 −3 m )>C 60 (2.2×10 −3 m )> 2 (1.9×10 −3 m )> 1 (1.7×10 −3 m )> 4 (1.4×10 −3 m )> 3 (1.0×10 −3 m ).…”
Section: Fullerenes Solubilized In Water By Natural‐product‐based Solmentioning
confidence: 99%
“…These γ‐CDx ⋅ C 60 derivative complexes are expected to broaden the potential applications of fullerenes. For example, C 60 derivatives 1 – 5 (Figure ) form 2:1 complexes with γ‐CDx through the HSVM method . The solubilities of the γ‐CDx ⋅ C 60 derivative complexes in water were in the following order: 5 (2.4×10 −3 m )>C 60 (2.2×10 −3 m )> 2 (1.9×10 −3 m )> 1 (1.7×10 −3 m )> 4 (1.4×10 −3 m )> 3 (1.0×10 −3 m ).…”
Section: Fullerenes Solubilized In Water By Natural‐product‐based Solmentioning
confidence: 99%
“…3,6,7 The γ-CDx-complexed C 60 derivatives of 1−3 were found to be soluble in water at high concentrations (i.e., >1.0 mM), with solubility levels comparable to that of unmodified C 60 (2.2 mM).…”
Section: Introductionmentioning
confidence: 99%
“…3,5 In a recent publication, we reported that several functionalized C 60 derivatives, such as the Nmethylpyrrolidine, N,N-dimethylpyrrolidinium, and N-acetylpyrrolidine derivatives (1−3, Figure 1) of C 60 , could form stable complexes with γ-CDx using a mechanochemical highspeed vibration milling apparatus according to Komatsu's method. 3,6,7 The γ-CDx-complexed C 60 derivatives of 1−3 were found to be soluble in water at high concentrations (i.e., >1.0 mM), with solubility levels comparable to that of unmodified C 60 (2.2 mM). 6,7 These complexes possessed a 1:2 stoichiometry of the γ-CDx unit to the C 60 derivative and existed in a [2]pseudorotaxane conformation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…2 It should be noted that aggregation of fullerene molecules in an inclusion complex of fullerene with g-cyclodextrin C 60 /2g-CD is impossible. 234,235 Fullerenes in membranes. To predict or at least understand the biological properties of fullerenes and their behaviour in the body, one should know how they interact with lipid membranes.…”
Section: Iii3 Biomedical Applicationsmentioning
confidence: 99%